The effect of the sectoral composition of economic growth on rural and urban poverty - Benfica, Rui; Henderson, Heath (International Association for Research in Income and Wealth, 2021)
We examine the relationship between the sectoral composition of economic growth and the rural‐urban composition of poverty. To this end, we use a cross‐country panel dataset consisting of 146 rural and urban poverty “spells” for 70 low‐ and middle‐income countries. We find that rural (urban) poverty is highly responsive to agricultural (non‐agricultural) productivity growth. The effect of agricultural productivity growth on rural poverty is particularly strong for countries with little dependence on natural resources. We also find that growth in the share of employment in the non‐agricultural sector (i.e. structural transformation) reduces rural poverty, most notably for countries at a low initial level of development. These findings are robust to changes in key assumptions, including using alternative poverty lines. Finally, we use our estimates to examine the past contribution of different sources of economic growth to rural and urban poverty reduction across regions.